2014
DOI: 10.5761/atcs.oa.13-00243
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Efficacy of Mitral Valve Repair for Degenerative Mitral Regurgitation in the Elderly

Abstract: Purpose: The number of elderly patients who require surgical treatment for mitral regurgitation (MR) is increasing. However, the feasibility and efficacy of mitral valve repair in elderly patients are unclear. Methods: We retrospectively reviewed 55 patients, aged ≥75 years, who underwent mitral valve repair for degenerative MR between 1991 and 2011. All patients were followed up for 4.7 ± 3.4 years. Results: The patients aged ≥75 years were more symptomatic and had a higher incidence of persistent atrial fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…There has been increasing discussion on the greater risks of cardiac surgery for the elderly. [2][3][4][5][6] On the other hand, over the past decade, technical improvements in cardiac surgery, better methods of myocardial protection, and advances in perioperative care have made valve surgery a viable option even for elderly patients. 3,7) Combined valve surgery requires longer operative times because of time required for CPB and AXC.…”
Section: Discussionmentioning
confidence: 99%
“…There has been increasing discussion on the greater risks of cardiac surgery for the elderly. [2][3][4][5][6] On the other hand, over the past decade, technical improvements in cardiac surgery, better methods of myocardial protection, and advances in perioperative care have made valve surgery a viable option even for elderly patients. 3,7) Combined valve surgery requires longer operative times because of time required for CPB and AXC.…”
Section: Discussionmentioning
confidence: 99%
“…However, the long term prognosis of surgically treated MR patients with PH, which included more aged patients, was still worse than that of patients without PH [23] . Murashita et al reported that preoperative PH disappeared after surgery in degenerative MR patients, and the leading cause of cardiovascular death after surgery was stroke, and most of patients who had recurrence of PH suffered from AF, which suggested recurrent PH after surgery was caused by different pathophysiology due to PH before surgery [24] .…”
Section: Discussionmentioning
confidence: 99%
“…Isolated oMVR for FMR is associated with an operative mortality between 0% and 7%. 6,23,24,[26][27][28] A recent publication which reviewed oMVP versus oMVR in elderly patients concluded despite the lack of RCT availability, oMVR was superior to oMVP with regards to mortality and postoperative complications. 29 The result suggest an advantage of oMVR compared to oMVP but randomized trials comparing oMVR with oMVP have been lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the authors give the recommendation of an individual assessment of oMVR in FMR. Isolated oMVR for FMR is associated with an operative mortality between 0% and 7% . A recent publication which reviewed oMVP versus oMVR in elderly patients concluded despite the lack of RCT availability, oMVR was superior to oMVP with regards to mortality and postoperative complications…”
Section: Discussionmentioning
confidence: 99%